Sejarah Empat Mazhab Islam dan Eksistensinya di Indonesia - Alfatoni, Muhammad Aqil; Ni’matul Wasih, Imelda; Hikmal Akbar, Mohammad; Nur Niba, Nadia Oktavia (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
Islamic law as we know and understand it has undergone several phases. Starting at the time of the Prophet untilnow. The Prophet has laid the foundation of the law which is upheld by the companions. This research the authorwants to know why many Indonesian people prefer to apply or use the Shafi'i Madzhab. This paper uses empiricallegal methods, with a qualitative approach and historical approach. The data collection technique that the authoruses is a questionnaire distributed to 33 respondents regarding why the general public applies more teachings from the Shafi'i madhhab and through journals and books, so that in this paper using qualitative research. The four main Sunni madhhabs have characteristics that distinguish each other in their interpretation of Islamic law. Despite their differences, the four madhhabs share the same goal of providing legal guidance to Muslims and maintaining the unity of the ummah. The methodology used by the four madhhab imams is certainly different in determining Islamic law. In Indonesia, the Shafi'i madhhab is the most dominant. The majority of scholars, Islamic boarding schools, and Islamic religious education institutions in Indonesia follow the Shafi'i madhhab in interpreting Islamic law. This is influenced by the history of Islam in Indonesia, where most of the spreaders of Islam in Indonesia were of the Syafi'i school of thought.